Shakespeare’s The Tempest Revisited: Nietzsche and the Myth of the New World - Burzyńska, Katarzyna (Studia Anglica Posnaniensia, 2019)
The Tempest is the only play in the Shakespearean canon that is open to a purely “Americanist” reading. Although Prospero’s island is located somewhere in the Mediterranean, numerous critics claimed that it deals with the New World (Hulme & Sherman 2000: 171). The paper revisits the existing interpretations, focusing on the turbulent relationship between Prospero and other inhabitants of the island: Caliban, Miranda, and Ariel. In the article I propose a rereading of their relation in the spirit of Friedrich Nietzsche’s perspectivism, utilising Nietzsche’s key philosophical concepts like the Apollonian/Dionysian elements and der Übermensch (the overman). In his vast canon, Nietzsche refers to Native Americans only once and in passing. However, his call for the revaluation of all values seems to be an apt point of departure for a discussion on early colonial relations. Nietzsche’s perspectivism enables to reread both the early colonial encounters and character relations on Shakespeare’s island. Hence, in an attempt at a “combined analysis”, the paper looks at Prospero as the potential overman and also offers a reading of the English source texts that document early encounters between the English and native inhabitants of North America (Walter Raleigh, Richard Hakluyt, Thomas Harriot, Robert Gray).